MASALAH HAK MANTAN ISTRI DAN ANAK TERHADAP GAJI PEGAWAI NEGERI SIPIL AKIBAT PERCERAIAN - Smithro Moestafa (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT That the technical execution of the ex-wife's right to the salary of her ex-husband, the division of salary if the divorce occurs because of the wishes of the Civil Servant of man then his salary is divided as follows: If no child, then ½ for the Civil Servant concerned; For ½ part wife; If having children and children join the Civil Servant concerned, then 2/3 for the Civil Servant concerned and his / her child and 1/3 for the wife.That the legal consequences of divorce are as follows: At the level of talaq ba'in, is a divorce that has entered the level of talaq three where the married couple is forbidden to reconcile before the former wife marries first with another person then the person divorces her; Divorce due to li'an, then marriage can no longer be done forever; Collective property is shared between husband and wife while the cost of maintenance and education is the responsibility of the father; The more entitled to take care of his children is his mother, as long as the mother is married to someone else.